Heart disease in eosinophilic granulomatosis with polyangiitis (EGPA) patients: a screening approach proposal. (26th January 2021) - Garcia-Vives, Eloi; Rodriguez-Palomares, J F; Harty, Len; Solans-Laque, Roser; Jayne, David
Abstract: Objective: To define the pattern of cardiac involvement in eosinophilic granulomatosis and polyangiitis (EGPA) and propose an algorithm for heart disease screening. Methods: This was a retrospective study of EGPA patients attending a specialized vasculitis clinic (1989–2016). Clinical characteristics and cardiovascular evaluation (CE) results (serum troponin, ECG, echocardiography and cardiac magnetic resonance) were collected and compared according to symptoms and inflammatory cardiac disease (ICD). Results: A total of 131 EGPA patients were included, of whom 96 (73%) had undergone CE. The median (interquartile range) age was 50 (38–58) years and 36% showed ANCA+. Asthma preceded diagnosis by a median of 97 (36–240) months. Among the 96 patients who underwent CE, 43% were symptomatic, with dyspnea (47%) and chest pain (29%) being the predominant symptoms. In asymptomatic patients, CE reported abnormalities in 45% of cases, with a subsequent earlier diagnosis (4 vs 11 months). Overall, 27 patients had EGPA-related ICD (EGPA-rICD) that was already present at diagnosis in 20 cases, preceded it in 2 cases and developed later in 5 cases. EGPA-rICD patients were younger (46 vs 50 years; P  = 0.04), had more frequently abnormal ECG (30.8 vs 2.1%; P  < 0.001), negative ANCA (85 vs 69%; NS), higher BVAS score (3 vs 1; P  = 0.005), higher eosinophil count (5.60 vs 1.60 × 10 9 /l; P  = 0.029) and higher CRP (52 vs 15 mg/l; P  = 0.017). Overall, 11% of cases with EGPA-rICD were asymptomatic. Conclusion: In our study, 45% of asymptomatic patients had an abnormal baseline cardiac evaluation, which allowed an earlier diagnosis of cardiac disease. We recommend prompt cardiac screening in all EGPA patients, instead of a symptoms-guided algorithm.